Estilo de Aprendizaje Visual: una estrategia educativa para el desarrollo de la memoria a largo plazo - Pullas, Paul Santiago (Journal of Learning Styles, 2017)
This article presents the results of the investigation based in the visual learning style as a strategy for long-term memory which it aims to create a better process in the knowledge acquisition to help students. In this way, the visual style will make easier to the student retain information for a long-term. In adittion, this article contains a theorical description about the learning styles and memory. In this investigation has been elaborated two measuring instruments that was applied to 40 students belonging to seventh year in the Teaching Unit Francisco Flor in three phases: an initial screening, an observation datasheet with the application of encourage activities, and a final test. Following, the analysis and interpretation of datum was realized and the verification of the hypothesis too. The results of the initial test and the final test were weighted; with it can calculate the Z-Test. It shows that exist a development of the memory in the long-term by educational strategies.
Keywords: aprendizaje